Semi-Occluded Vocal Tract Exercises: Aerodynamic and Electroglottographic Measurements in Singers - Dargin, Troy Clifford; Searl, Jeff (Journal of voice, 2015)
The purpose of this study was to describe changes in aerodynamic and electroglottographic (EGG) measures immediately after completing three semi-occluded vocal tract (SOVT) exercises. Prospective case series. Aerodynamic and EGG measurements were obtained before and immediately after performing three SOVTs (straw phonation, lip trill, and tongue trill) in four singers for prepost comparisons to evaluate laryngeal changes persisting beyond the execution of SOVTs. Mean air flow, sound pressure level, and EGG closed quotient tended to increase after completing SOVTs. The magnitude of change and consistency of change in measures across the SOVTs varied from subject-to-subject. Aerodynamic and EGG changes did occur during and immediately after completing SOVTs. However, there was marked variability within and across participants. Further investigation is needed to better understand which SOVTs are likely to benefit a particular individual.